Mental health crisis in children and adolescents: The hidden harm of COVID-19 - Saraiva, Joana (2022)
Given the atypical scenario caused by the COVID-19 pandemic in recent years and the changes it brought to daily routines, particular attention should be paid to the mental health of children and adolescents. During this period, child and adolescent psychiatrists faced challenges in their clinical practice and had to adjust to the new reality. There was a significant increase in consultation referrals due to eating disorders, self-harm behaviors, and anxiety symptoms. This paper describes the experience of the Department of Child and Adolescent Psychiatry of Centro Materno-Infantil do Norte, Centro Hospitalar Universitário do Porto, in the outpatient, inpatient, and Emergency Room care of children and adolescents in different age groups during this period. It also highlights the need for special attention to the psycho-affective development of these groups and to the role of family and school. Overall, the pandemic had a number of detrimental effects on children and adolescents, but also on their families. At this time, it is still difficult to ascertain what long-term consequences it will have, particularly in the first years of life. Joint efforts should be employed by health and community systems to create adequate conditions for assessing the mental health of these groups and developing appropriate support and prevention strategies.